An analysis of Lecturer Perception on the Use of E-learning for English Instruction in IAIN Kendari - Zulfahmi MD, Sarwo; Tanduklangi, Amri; Mursalim, Mursalim (Halu Oleo University, 2018)
The purpose of this study is to assess perceptions of english lecturers in IAIN Kendari and how their perceptions relate to e-learning integration. The design of this study is descriptive-qualitative research. Semi-structured interviews with 7 open-ended questions are used for collecting data. Informants are 6 instructors who have used e-learning system to teach IAIN Kendari students. Comparing lecturers’ perceptions with the related literature, coded data were grouped into 7 themes for answering research problem and research questions. The findings revealed that: (a) lecturer perceived five e-learning strengths on English instruction. They are; multiple function, lecturers workload, autonomous learning, increasing motivation, and user friendly. (b) Lecturers’ perceptions concerning the weaknesses of e-learning are pubbing, consuming time, attitude problem, and less creative. (c) Lecturers’ perception regarding student reaction on e-learning is more motivation, significant impact, interesting, and unconfident (d) lecturers experienced 7 hindrances on the use of e-learning, they are student devices, instability of internet, high cost, distraction, high energy, willing not to use, and digital literacy. (e) by English lecturers experiences, Institution support e-learning implementation with wi-fi, computer lab, online management, IT expert, and official e-learning training by TIPD. (f) Preferred features used by English lecturers are browsing, chatting, teaching aid, online discussion, and multimedia sharing. (g) English lecturers improved e-learning ability by official training in campus, official events, distance class, peer-assisted, self-taught learner, and reflection. In short, lecturer perceptions have significant impact in implementing e-learning for English insruction. The integration quality of e-learning based on the lecturer understanding of e-learning in which will influence English skill of students. For recomendations, Lecturers should work together to use more high level integration tools to solve problems. With adequate support, encouragement and accessibility, lecterurs will have more succes with technology integration.